Leading article - Reyes, Pedro (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
Beyond providing education to professionals and researches, a university’s fundamental duty is to create knowledge as the base of human activity in society. The diffusion of this knowledge is also a fundamental task. As the School of Journalism at the Universidad de Santiago, we wish to honor this duty and relaunch the Re-Presentaciones journal, an academical mean of diffusion that has existed for around five years in our academic unit.